Kajian Pragmatik terhadap Tindak Tutur Lokusi, Ilokusi, dan Perlokusi pada Interaksi Pedagang dan Pembeli di Pasar Pagi Songgolangit Ponorogo - Lisma Meilia Wijayanti (Lingua Franca, 2025)
This study aims to examine the use of locutionary, illocutionary, and perlocutionary speech acts in interactions between sellers and buyers at the Songgolangit Morning Market, Ponorogo. Employing a qualitative descriptive approach, the data were collected through audio recordings of natural conversations during buying and selling activities at six vegetable shops. The recorded interactions were transcribed and analyzed using a pragmatic framework based on speech act theory proposed by Austin and developed by Searle. The findings indicate that all three types of speech acts—locutionary, illocutionary, and perlocutionary—appear consistently and simultaneously in market interactions. Locutionary acts function to convey literal information such as product types, quantities, prices, and personal narratives. Illocutionary acts are the most dominant, primarily realized through directives, negotiations, requests, and expressions that reflect the speakers’ communicative intentions. Perlocutionary acts are manifested through concrete responses and actions, including weighing goods, handing over items, giving price reductions, and completing transactions, which demonstrate the effectiveness of communication. This study confirms previous research that highlights the dominance of illocutionary speech acts in traditional market transactions. However, it also offers novelty by emphasizing the significant role of personal narratives and expressive speech acts in fostering social closeness and trust between sellers and buyers, which contribute to smoother transactions. The results suggest that traditional markets function not only as economic spaces but also as social interaction arenas rich in pragmatic practices. This research is expected to contribute theoretically to pragmatic studies, particularly speech act analysis, and practically to a deeper understanding of everyday language use in public spaces.